Differences between current clinical guidelines for screening, diagnosis and management of nonalcoholic fatty liver disease and real-world practice: a targeted literature review. (2nd November 2021) - Schattenberg, Jörn M; Anstee, Quentin M; Caussy, Cyrielle; Bugianesi, Elisabetta; Popovic, Branko
ABSTRACT: Introduction: Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease and is associated with obesity and metabolic comorbidities. Liver steatosis can progress to nonalcoholic steatohepatitis (NASH) exhibiting a relevant risk of fibrosis and ultimately liver failure. To date, no approved treatment for NASH to reduce its clinical and humanistic burden has been developed. Areas covered: We undertook a literature review to identify English language, national and international clinical guidelines for NAFLD regarding diagnosis, assessment and management, and determined their points of agreement and difference. Additionally, we investigated published literature relating to real-world management of NAFLD and NASH. Expert opinion: National (China, England/Wales, Italy, the USA) and international society (Asia-Pacific, Europe, World Gastroenterology Organization) guidelines were identified and analyzed. All guidelines addressed identifying and diagnosing subjects with likely NAFLD, as well as assessment and management of individuals with risk factors for advanced disease, including fibrosis. Real-world practice reveals widespread suboptimal awareness and implementation of guidelines. In the absence of proven therapeutics, such gaps risk failure to recognize patients in need of specialist care and monitoring, highlighting the need for clear, easy-to-apply care pathways to aid in reducing the clinical and humanistic burden of NAFLD and NASH.